Gelingensbedingungen von Schulreform Bildungshistorische Befunde als Schlüssel zum pädagogischen Verständnis von Schulentwicklungsprozessen und als Erweiterung des Theorienverbundes zur Schulreform - Link, Jörg-W (Historische Bildungsforschung, 2023)
This work presents a structural and operative model of successful processes of school reform, based on eleven source-based studies on the history of educational and school-based pedagogy. Oriented on real-world cases and sources, these studies analyse the reform practices of historical reform schools during the twentieth century. The point of reference in each case is the individual school as a pedagogical unit of action. The studies are historically and empirically grounded and provide in-depth insights into the historical practices of schools as well as historical school reforms. The term "conditions for success" is employed here to focus on organisational structures and pedagogical patterns of action within historical processes of reform. The findings are derived from the inherent logic of practical pedagogical processes of reform. These are structures and patterns of action developed by the pedagogical professionals themselves through social processes. The results of the educational-historical source studies are collated here in a model of recurring professional patterns of pedagogical action and structure. The resulting historically and empirically developed "Five-plus-two-K Structure of Successful School Reform Processes" was tested on 100 modern day reform schools and it could be shown that these processes recur over a period of about one hundred years. Following the inherent logic of pedagogical processes in schools, the "Five-plus-two-K Structure of Successful School Reform Processes" was developed through a process of professional pedagogical action, shaped by professional pedagogical action and interaction, and was differentiated for professional pedagogical action. This model is integrative on the basis that it is primarily pedagogically constituted and was closely developed with educational professionals. The model is thus an educational-historical contribution to a theory of school reform processes and contributes to the pedagogical understanding of the processes of school development.